Evaluasi Kepuasan Pengguna Aplikasi E-Book-Ku Universitas Amikom Purwokerto Dengan Metode UTAUT - Susilo, Deni Dwi; Pratama, Riski Adhi; Mubarok, Rifqi; Haqqi, Matsnan; Setiawan, Ito (STMIK KAPUTAMA, 2025)
This research aims to analyze user experience on the level of user satisfaction of the application E-Book-Ku application at Amikom Purwokerto University, using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Theory of Acceptance and Use of Technology (UTAUT) model. This research using a quantitative approach with data collection through a questionnaire distributed to students of Amikom Purwokerto University as users of the E-Book-Ku application. E-Book-Ku application. The variables studied consisted of Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), Facilitating Conditions (FC), Behavioral Influence (BC), and Behavioral Behavior (BC). (SI), Facilitating Conditions (FC), Behavioral Intention (BI), and Use Behavior (UB). Data were analyzed using validity test, reliability, and hypothesis testing to test the relationship between variables using SmartPLS. using SmartPLS. The results showed that all hypotheses accepted, where Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions have a positive and significant effect on Behavioral Intention. and significant on Behavioral Intention. In addition, Behavioral Intention is proven to have a positive influence on Use Behavior. This finding indicates that user satisfaction in using the E-Book-Ku application is influenced by ease of use. E-Book-Ku application is influenced by the ease of use of the application, social support from the surrounding environment, and the availability of facilitating conditions. environment, and the availability of conditions that facilitate the use of application. This research contributes to application managers to improve the aspects that influence user experience in order to increase the level of satisfaction and use of the application among students. Keywords: User Satisfaction, Application E-Book-Ku, UTAUT Method, SmartPLS.